Analisis Faktor Kepatuhan Berobat Penderita Tuberculosis Paru di Bandung - Upik Rahmi (Wiraraja Medika : Jurnal Kesehatan, 2020)
ABSTRACT Tuberculosis (TB) is one of the public health problems that cannot be overcome. The problem is caused by several factors, one of which is the non-compliance of patients with treatment. In Indonesia, the incidence of TB cases is 842,000 per year and notification of TB cases is 569,899 cases, so there are still around 32% of the cases that have not been verified either unreached, undetected or not reported. From this incident rate the TB burden is calculated in each province and district / city, (Indonesia, 2019). Purpose: Identify factors related to adherence to the treatment of pulmonary TB patients in the working area of ​​Garuda Bandung Puskesmas. Method: This is an analytic case study with a case control design. The sample of this study was 43 pulmonary TB patients taken in total who failed and were removed from treatment in 2017. The research instrument used a questionnaire. Data analysis using chi square. Results: The most dominant factors affecting adherence to treatment among pulmonary TB patients were Gender P value (0.014) and occupational Pvalue (0.025) where p <0.05 while factors not related to medication adherence were age, knowledge, education, and family income, p> 0.05. Conclusion: Gender and occupation have a significant relationship to tuberculosis treatment adherence, while age, knowledge and family income have no significant relationship to tuberculosis patient adherence. Keywords: Pulmonary tuberculosis, compliance, Medicine